Isolation and Sequencing of Chromosome Arm 7RS of Rye, Secale cereale - Petereit, Jakob; Tay Fernandez, Cassandria; Marsh, Jacob I; Bayer, Philipp E; Thomas, William J W; Aliyeva, Aybeniz Javad; Karafiátová, Miroslava; Doležel, Jaroslav; Batley, Jacqueline; Edwards, David (International journal of molecular sciences, 2022)
Rye (Secale cereale) is a climate-resilient cereal grown extensively as grain or forage crop in Northern and Eastern Europe. In addition to being an important crop, it has been used to improve wheat through introgression of genomic regions for improved yield and disease resistance. Understanding the genomic diversity of rye will assist both the improvement of this crop and facilitate the introgression of more valuable traits into wheat. Here, we isolated and sequenced the short arm of rye chromosome 7 (7RS) from Triticale 380SD using flow cytometry and compared it to the public Lo7 rye whole genome reference assembly. We identify 2747 Lo7 genes present on the isolated chromosome arm and two clusters containing seven and sixty-five genes that are present on Triticale 380SD 7RS, but absent from Lo7 7RS. We identified 29 genes that are not assigned to chromosomal locations in the Lo7 assembly but are present on Triticale 380SD 7RS, suggesting a chromosome arm location for these genes. Our study supports the Lo7 reference assembly and provides a repertoire of genes on Triticale 7RS.
Keywords: Secale; chromozomy rostlin; žito; Edible Grain; Chromosomes, Plant; Triticum; Disease Resistance; pšenice; presence-absence variation; odolnost vůči nemocem; isolated chromosome arm sequencing; jedlá semena; triticale; Triticale; rye